ANALYSIS OF ECOSYSTEM MATERIALS ON SCIENCE SKILLS OF ELEMENTARY SCHOOL STUDENTS - Tiara Zalza Nabilah; Ananda Roqiba Faradisi; Eka Aulia Sari (Media Inovasi Pendidikan dan Publikasi, 2023)
Science is one of the subjects taught in elementary school. They can help students better understand the situation of their surroundings and can bring students closer to nature. Science is oriented learning to define things, to develop thinking ability, to develop learning ability, to be responsible, and to care about the environment. In student science it is expected to also have another skill to develop - that of science-process skills (KPS). This KPS is a scientific skill possessed by a scientist for the acquisition of knowledge. As for the purpose of this article, it is to be able to find out how an analysis of ecosystem materials on elementary school student science skills. As for the method used in this study is the study of literature.